2002
DOI: 10.1093/ajhp/59.23.2346
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist time requirements for counseling in an outpatient pharmacy

Abstract: The correlation between the pharmacist time required for counseling patients and the characteristics of the services provided was studied.Data from the Kaiser Permanente/USC Patient Consultation Study were used to examine the relationship between pharmacist time and potential problems, actions to resolve the problems, and disposition of prescriptions. A regression model was estimated with pharmacist time as the dependent variable.An encounter consisting of patient contact to monitor adverse effects, duplicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…The literature advocates that pharmacists should designate at least 3 minutes per patient. 42 However, the amount of time the pharmacist spent in the current study was approximately half of this. In a similar study, 26 the CPs spent an amount of time with the patient that was on par with the present study.…”
Section: Discussionmentioning
confidence: 80%
“…The literature advocates that pharmacists should designate at least 3 minutes per patient. 42 However, the amount of time the pharmacist spent in the current study was approximately half of this. In a similar study, 26 the CPs spent an amount of time with the patient that was on par with the present study.…”
Section: Discussionmentioning
confidence: 80%
“…Johnson et al [14] compared the routine provision of pharmacist consultations to US outpatients with two experimental models: the socalled Kaiser Permanente (KP) model, which consisted of targeted pharmaceutical care services to high-risk patients (identified by their drug use); and the State of California (SC) model which consisted of mandated patient consultation to all patients with a new or changed refill prescription. They found that the control group recorded problems much less often than than the two experimental groups (20 and 10% of the SC group and KP group, respectively) and that two-thirds of the actions undertaken in the control group were not directed towards the patients themselves but to the prescribing physician [15]. Chen and Britten [16] analysed the content of personal consultations provided by UK community pharmacists, but this was a qualitative study of only 25 consultations, all of which took place within GP surgeries and in patients' homes.…”
Section: Introductionmentioning
confidence: 99%
“…That is, a joint consideration of the demand and supply factors is needed for assessing the purported lack of sufficient number of pharmacists in certain US regions, practice settings and position types. This investigation is also motivated by the fact that degreed pharmacists are no longer limited to sales and marketing, as knowledge of chemistry, pharmacology, pharmaceutics, management, etc., has made them more diversified and knowledgeable employees to a wider array of potential employers (Youlio, 1993;Drug Store News, 1993;Oh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%